A Comparative Study on the Nature of International Oil Buybacks and the Islamic Contracts - Fathollah Rahimi; Mir Shahbiz ' Shafe (پژوهش تطبیقی حقوق اسلام و غرب, 2015)
As the primary means of attracting foreign investment, international oil buybacks are consistent with the Iranian Law. Despite the criticisms available, they have been the financing source of the oil industry in Iran. It has been the legal basis of the interactive relationship between Iran and the oil company investors for almost two decades. The legal structure developed gradually, so today it is being unveiled as its new generation, dubbed as the Iranian petroleum contract. In this way, the Iranian legislature has prescribed both exploration and development meticulously, so that with changes in its content, it can receive benefits at the time when the country needs foreign investment especially in the shared oil fields. It will receive benefit with more use of external resources in order to exploit oil resources, particularly in the field of mutual benefit and the difficulty of financing. This paper is an attempt to examine this subject matter in an analytical way. It is an attempt to show the strengths and weaknesses of the oil buyback contracts in each of their generations and offer an applied research on the rise and appearance of the deformation and development of buyback processes in the context of the Iranian Legislature. Specifically, it wants to explain factors affecting development of the international oil contracts and describe the reasons for the recourses, the application and use of this method of signing contracts.